The Effect of Working Hours on Occupational Health and Safety Mediated by Work Stress: A Study on Grab Drivers in Kuningan City - ALFIANSYAH, Rifky (PT Batara Swastika Harati, 2023)
This study aimed to investigate the impact of working hours on the occupational health and safety of online transportation drivers mediated by work-related stress. The research was conducted to reduce the number of accidents involving online transportation drivers. This research employs associative quantitative research based on data that can be calculated to produce an evaluation. Eighty internet transportation drivers in kuningan City were given questionnaires to complete to gather primary data. The data was analyzed using structural equation modeling (SEM) for model and hypothesis testing with PLS 3.0 statistical software. The results indicate that working hours and stress significantly affect employee occupational safety and health. Additionally, working hours impact work stress. This study found that work stress may mediate the impact of working hours on occupational health and safety. Injuries or illnesses sustained at work may result from the stress experienced by driver-partners due to long working hours. The study's findings can help Grab and other online drivers organize their working hours to reduce work-related stress and, ideally, maintain safety.